STRATEGIC SECURITY ENVIRONMENT AND THE ROLE OF MILITARY ENGINEERING SUPPORT IN OPERATIONS - Pehlivanov, Svetlin (Horizons - International Scientific Journal, 2021)
The inclusion of Bulgarian Army in operations and missions led by NATO and the European Union requires a new approach by Bulgarian Armed Forces. The development of national adaptive capabilities of engineer units will contribute to the strengthening of the national security and defense of the country and to neutralizing the risks and threats where they arise. To fully leverage the capabilities of the Bulgarian Army requires enhancing engineer capabilities as well. This paper examines the influence of the current security environment to the Bulgarian Armed Forces. It further discusses the importance of the role of military engineering support in the operations. The goal of the paper is to implement a new approach for the development of engineer capabilities.